2000
DOI: 10.1038/emm.2000.16
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of resveratrol on proliferation and apoptosis in endothelial and tumor cell cultures

Abstract: Experimental data suggest that Resveratrol, a compound found in grapes and other fruits may influence cell proliferation and apoptosis. The aim of our experiments was to study the effect of Resveratrol on tumor cell cultures and an endothelial cell culture in order to examine the effect of various doses of this compound on active cell death and cell proliferation. Human tumor (HT-29, SW-620, HT-1080) and endothelial (HUV-EC-C) cells were treated with various doses of (0.1 to 100.0 µg/ml) Resveratrol in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
61
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 24 publications
(21 reference statements)
12
61
1
2
Order By: Relevance
“…Many authors have reported a protective role of lower dose RSV against certain cellular insults, including oxidative stress-induced apoptosis by ethanol and hydrogen peroxide, as well as drug-induced apoptosis in cancer cells. [13][14][15] In particular, RSV has been shown to be antagonistic to paclitaxel-induced apoptosis in breast cancer and neuroblastoma cells at lower doses between 1-100 μM. 16 These findings are concordant with our results, which demonstrated that lower dose RSV protected against 5-FU-evoked apoptosis in colon cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…Many authors have reported a protective role of lower dose RSV against certain cellular insults, including oxidative stress-induced apoptosis by ethanol and hydrogen peroxide, as well as drug-induced apoptosis in cancer cells. [13][14][15] In particular, RSV has been shown to be antagonistic to paclitaxel-induced apoptosis in breast cancer and neuroblastoma cells at lower doses between 1-100 μM. 16 These findings are concordant with our results, which demonstrated that lower dose RSV protected against 5-FU-evoked apoptosis in colon cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…Based on our observation it was revealed that although resveratrol treatment at the concentrations of 0.25 and 0.5 μM produce optimum effect the higher concentration of this (5 μM) has detrimental impact. This is in line with the earlier reports of dose-dependent effect exerted by resveratrol in cell proliferation [20,39] as well as mammalian embryonic development [21,24]. Supplementation of antioxidants in culture medium influences oocyte maturation and embryonic development.…”
Section: Discussionsupporting
confidence: 92%
“…Studies on HUVEC (human umbilical vein endothelial cells) demonstrated that the molecule at low concentrations induces the proliferation of this cell phenotype, while, at high doses, it causes HUVEC growth impairment and apoptosis. 93 The inhibition of angiogenesis was also confirmed in several other cell systems and in a three-dimensional model of tube formation. 88 Investigation on the mechanism(s) by which the hydroxystilbene inhibits VEGF-induced angiogenesis showed that resveratrol effectively abrogated VEGF-mediated tyrosine phosphorylation of vascular endothelial-cadherin and its partner, b-catenin.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 69%